Resuscitation of out-of-hospital cardiac arrests in residential aged care facilities in Melbourne, Australia - Deasy, C.; Bray, Janet; Smith, K.; Harriss, L.; Bernard, S.; Davidson, P.; Cameron, P. (2012)
Introduction: CPR in patients in residential aged care facilities (RACF) deserves careful consideration. We examined the characteristics, management and outcomes of out-of-hospital cardiac arrest (OHCA) in RACF patients in Melbourne, Australia. Methods: The Victorian Ambulance Cardiac Arrest Registry (VACAR) was searched for all OHCAs occurring in RACFs in Melbourne. The characteristics and outcomes were compared to non-RACF patients in the VACAR. Results: Between 2000 and 2009 there were 30,006 OHCAs, 2350 (7.8%) occurring in a RACF.A shockable rhythm was present in 179 (7.6%) patients on arrival of paramedics of whom bystander CPR had been performed in 118 (66%); 173 (97%) received an EMS attempted resuscitation. ROSC was achieved in 71 (41%) patients and 15 (8.7%) patients survived to leave hospital. Non shockable rhythm was present in 2171 patients (92%) of whom 804 (37%) had an attempted resuscitation by paramedics. ROSC was achieved in 176 patients (22%) and 10 patients (1.2%) were discharged alive. Survival from OHCA occurring in a RACF was less than survival in those aged >70 years of age who suffered OHCA in their own homes (1.8% vs. 4.7%, p=0.001). On multivariable analysis, witnessed OHCA (OR 3.0, 95% CI 2.4-3.7) and the presence of bystander CPR (OR 4.6, 95% CI 3.7-5.8) was associated with the paramedic decision to resuscitate. Conclusion: Resuscitation of patients in RACF is not futile. However, informed decisions concerning resuscitation status should be made by patients and their families on entry to a RACF. Where it is appropriate to perform resuscitation, outcomes may be improved by the provision of BLS training and possibly AED equipment to RACF staff. © 2011 Elsevier Ireland Ltd.